Doc, I Think I Got Something Stuck - Michael Waldrop; Matthew Sarsfield; Elliot Rodriguez (Association of American Medical Colleges, 2015)
Abstract Introduction One mantra of emergency care is "no airway, no patient." However, when teaching basic life support and advanced cardiovascular life support (ACLS) management of critical patients, the cardiac support is often emphasized over the airway management. Given the importance of the specific skill of airway management, this simulation focuses on airway management using high-fidelity adult simulation mannequins. Methods This simulation case is designed to last approximately 15-20 minutes. During this time participants must assess the patient and collect a medical history, recognize the presence of a critical airway threat, and take appropriate steps to reclaim the airway. Results This case has had three trial runs with a total of seven medical students. In general the reception from these medical student learners was positive. Overall, they endorsed that the case enhanced their future clinical practice. In response to the question "One thing I learned that I can use to improve my clinical practice," one participant reported "The fact that McGill forcepts exist [sic]" and another stated "...Also the McGill forceps were helpful to see [sic]." Discussion Initially it was our intention to create this simulation for a pediatric patient, but the overly narrow tracheal and laryngeal diameter of our facility's pediatric mannequin precluded this possibility. The case could be adapted to a child with only minor changes, such as: beginning with a pediatric high-fidelity mannequin and then switching to an airway task trainer or adult high-fidelity mannequin for the steps of airway management; modifying the historical and social factors to be age appropriate.